Palladio and the Mediterranean heritage the patio, atrium and portico as geometrical and well-being strategies - de Jorge-Huertas Virginia; de Jorge-Moreno Justo (Spatium, 2019)
Palladio’s heritage has aspects that are interrelated with the vernacular architectural heritage of the Mediterranean, and it entails a collective knowledge. The aim of this research is to analyse his work and its evolution over time, paying specific attention to three architectural design elements: the patio, the portico and the atrium in relation to their proportions and ratios. This work will highlight how geometry shapes the space and the form of these three elements, producing architecture for well-being. The main results may constitute a possible new frontier of research where these three design elements make a connection between interior and exterior spaces, strengthen a greater visibility of the geometry, create “intermediate spaces” and enhance the idea of a “Continuous Monument”. The paper will underline how mathematical factors such as proportions, ratios and constructive geometry, together with climatic reasons, are important in architecture for both its configuration and geometry and they are a constant in Palladio’s heritage and his Mediterranean cultural influence.